The Influence of Brand Image on Purchasing Decisions Toyota Agya at PT Auto2000 Asia Afrika Bandung - Hesti Sugesti; Aulia Syifa Fadhillah; Haiqal Abdillahsk; Angga Dewi Anggraeni (IAEI, 2023)
Based on brand perception and purchase intent, the purpose of this study is to ascertain whether the Toyota Agya automobile in auto2000 influences consumers' decisions to buy. Quantitative research is used in this study. The relationship between a number of variables is demonstrated by this research. With 99 respondents who work as service providers at auto2000 in the city of Bandung, this study takes a descriptive approach. Buying decisions (Y) and brand image (X) are the study's variables. A questionnaire is the tool used to collect the data. Simple linear regression analysis and descriptive analysis are the data analysis techniques employed. Version 25.0 of SPSS for Windows is used by data processing tools. Purchase decisions are significantly and favorably impacted by brand image, according to the findings of simple linear regression analysis. This clarifies why PT.Auto2000 Asia Afrika Bandung's Toyota Agya purchasing decision-making process is positively influenced by brand image.